Perturbations in common and distinct inflammatory pathways associated with morning and evening fatigue in outpatients receiving chemotherapy. (14th November 2022) - Kober, Kord M.; Harris, Carolyn; Conley, Yvette P.; Dhruva, Anand; Dokiparthi, Vasuda; Hammer, Marilyn J.; Levine, Jon D.; Oppegaard, Kate; Paul, Steven; Shin, Joosun; Sucher, Anatol; Wright, Fay; et al.
Abstract: Background: Moderate to severe fatigue occurs in up to 94% of patients with cancer. Recent evidence suggests that morning and evening fatigue are distinct dimensions of physical fatigue. The purposes of this study were to evaluate the transcriptome for common and distinct perturbed inflammatory pathways in patients receiving chemotherapy who reported low versus high levels of morning or low versus high levels of evening cancer‐related fatigue. Methods: Patients completed questionnaires during the week prior to their chemotherapy treatment. Severity of morning and evening fatigue was evaluated using the Lee Fatigue Scale. Gene expression and pathway impact analyses (PIA) were performed in two independent samples using RNA‐sequencing ( n  = 357) and microarray ( n  = 360). Patterns of interactions between and among these perturbed pathways were evaluated using a knowledge network (KN). Results: Across the PIA, nine perturbed pathways (FDR < 0.025) were common to both morning and evening fatigue, six were distinct for morning fatigue, and four were distinct for evening fatigue. KN (19 nodes, 39 edges) identified the phosphatidylinositol 3‐kinase (PI3K)‐Akt pathway node (perturbed in evening fatigue) with the highest betweenness (0.255) and closeness (0.255) centrality indices. The next highest betweenness centrality indices were seen in pathways perturbed in evening fatigue (i.e., nuclear factor kappa B: 0.200, natural killer cell‐mediated cytotoxicity: 0.178, mitogen‐activated protein kinase: 0.175). Conclusions: This study describes perturbations in common and distinct inflammatory pathways associated with morning and/or evening fatigue. PI3K‐Akt was identified as a bottleneck pathway. The analysis identified potential targets for therapeutic interventions for this common and devastating clinical problem. Abstract : This study describes perturbations in common and distinct inflammatory pathways associated with morning and/or evening fatigue associated with clinically meaningful levels of morning and evening fatigue severity in oncology patients receiving chemotherapy. A knowledge network represents the pathway‐to‐pathway interconnections of common and distinct perturbed inflammatory pathways. The distinct pathways for morning (blue nodes) and evening (red nodes) fatigue group together within the knowledge network. The remaining interconnections between the two symptoms are common perturbed pathways (green nodes). PI3K‐Akt was identified as a bottleneck pathway. The analysis identified potential targets for therapeutic interventions for this common and devastating clinical problem.